Mental illness-related stigma and its associated factors among primary health care professionals in rural China - Yi-Yue Yang; Yi-Yue Yang; Cong Wang; Cong Wang; Jia Cai; Jia Cai; Yun-Fei Mu; Yun-Fei Mu; Lie Zhou; Lie Zhou; Yi-Zhou Wang; Tian-Ming Zhang; et al. (Frontiers in Psychiatry)
BackgroundPrimary health care professionals (PHCPs) play a key role in the workforce of community mental health services in rural China. This study aimed to explore the mental illness-related stigma and its associated factors among PHCPs in rural communities.MethodsThis study collected the data from 247 PHCPs in 10 township health service centers in Xinjin District, Chengdu, Sichuan Province, China from November to December 2023. The Mental Illness: Clinicians’ Attitudes (MICA) was used to assess the mental illness-related stigma. Demographic and stigma-related psychological scales were compared between PHCPs with and without mental illness-related stigma. Correlation and binary logistic regression analyses were performed.ResultsThere were 155 PHCPs (62.8%) with mental illness-related stigma, and the mean score of MICA was 50.68 ± 8.08. PHCPs with mental illness-related stigma had significantly lower mean scores of the Mental Health Knowledge Schedule (MAKS), the Reported and Intended Behavior Scale (RIBS), the 5-item Contact Scale (CQTS), and the 5-item Contact Quality Scale (CQLS) (p=0.001, p<0.001, P=0.041, P<0.001), and higher mean scores of the Social Distance Scale (SDS) (p<0.001) than those without mental illness-related stigma. Binary logistic regression analysis showed that PHCPs’ work experience (β=0.080, 95%CI=1.002~1.170, p=0.044) and scores of SDS (β=0.169, 95%CI=1.056~1.328, p=0.004) had significantly positive impact on the mental illness-related stigma, and the scores of MAKS (β=-0.082, 95%CI=0.850~0.998, p=0.045) and RIBS (β=-0.131, 95%CI=0.783~0.983, p=0.024) had significantly negative impact on the mental illness-related stigma.ConclusionsThe PHCPs have severe mental illness-related stigma in rural China, and the associated factors include work experience, mental health knowledge, behavioral discrimination, and social distance towards people with mental illness. The results of this study are crucial for development of anti-stigma intervention among PHCPs in rural communities.